No Refuge Here. - Huff-Hannon, Joseph (Dissent (0012-3846))
The article examines the immigration policy of the U.S. government that affects several Iraqi refugees. In 2006, during the four-year anniversary of the U.S.-led invasion in Iraq, less than 500 Iraqis were given the refugee status by the Bureau of Population, Refugees and Migration among the 40,000 refugee applicants. According to the Migration Policy Institute, more than a third of Iraqis living in the U.S. originally entered as refugees or were granted refugee status. In April 2007, the members of the United Nations High Commission for Refugees (UNHCR) had gathered to address the financial, economic support and to expand resettlement opportunities.